2008
DOI: 10.1007/s10812-008-9070-1
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic determination of binding between human serum albumin and a platinum(II) dimethylsulfoxide complex

Abstract: We have used electronic absorption and fluorescence spectroscopy to study binding between a platinum(II) dimethylsulfoxide complex (cis-[Pt(DMSO) 2 Cl 2 ]) and human serum albumin (HSA), and the effect of complexation on the structure of the protein. We have calculated the binding parameters for binding between cis-[Pt(DMSO) 2 Cl 2 ] and HSA. We have determined the binding constant K B = (1.2 ± 0.1)⋅10 3 M -1 and the Hill coefficient h = 1.03 ± 0.1. We have determined that binding between cis-[Pt(DMSO) 2 Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…9). The BSA characteristic bands at 217 and 279 nm are assigned to constituent amino acids of serum albumins [33,34]. Especially, the band at 279 nm mainly originates from aromatic residues and disulfide bonds in the protein [35].…”
Section: Electronic Spectramentioning
confidence: 99%
“…9). The BSA characteristic bands at 217 and 279 nm are assigned to constituent amino acids of serum albumins [33,34]. Especially, the band at 279 nm mainly originates from aromatic residues and disulfide bonds in the protein [35].…”
Section: Electronic Spectramentioning
confidence: 99%
“…The results suggested that the binding between valsartan and the protein did not lead to a change in the polarity of the microenvironment of the Trp and Tyr residues; however, the internal packing of the protein changed (28). Furthermore, the results suggested that valsartan predominantly binds to Trp residues, but this binding does not appear to induce large structural changes in the microenvironment around the Trp residues.…”
mentioning
confidence: 91%
“…e absorption of inorganic-iodine, such as − , is certainly bound to serum albumin. Serum albumins, human serum albumin (HSA), and bovine serum albumin (BSA) play an important role in the transport and disposition of a wide variety of substances like metals, fatty acids, amino acids, hormones, and drugs [2][3][4][5][6]. Competitive interactions in the aqueous solutions containing DMSO and ions were a subject of numerous studies [7,8].…”
Section: Introductionmentioning
confidence: 99%